The influence of transformational leadership style and work environment on organizational commitment with work motivation as a mediating variable - Nanang Ismail Raharjo; Siti Nur Azizah (Jurnal Mantik, 2024)
Organizational commitment is crucial for employee loyalty and success in a globalized world. It is essential for the survival of a school and the success of its goals, especially in the face of competition. This study aims to examine and evaluate the influence of transformational leadership style and work environment on organizational commitment, with work motivation as a mediating variable. Data collection was carried out through questionnaires distributed to 42 teachers and employees at SMAN 1 Mirit, Kebumen Regency. Structural equation modeling (SEM) using the SmartPLS 3 (Partial Least Squares) program is used for analysis. The study's findings reveal the following: Transformational Leadership (X1) has a significant effect on Work Motivation (Z), Work Environment (X2) has a significant effect on Work Motivation (Z), Transformational Leadership (X1) has no significant effect on Organizational Commitment (Y), Work Environment (X2) has a significant effect on Organizational Commitment (Y), Work Motivation (Z) has a significant effect on Organizational Commitment (Y), Transformational Leadership (X1) has a significant effect on Organizational Commitment (Y) mediated by Work Motivation (Z),and Work Environment (X2) has a significant effect on Organizational Commitment (Y), mediated by Work Motivation (Z).